Sulfide elimination by using an aerobic sequencing batch reactor - Nissa Dayanah, Mohd Anuar (2016)
Several industries such as petrochemical, tanneries and photographic are producing high strength effluent containing sulfide and chemical oxygen demand (COD). Previous studies indicated that the elimination of sulfides was feasible by using physicochemical, chemical, and biological techniques. Although, physicochemical and chemical treatments have potential for high removal efficiency but it still have limitations due to high operational cost and restricted application in small scale facilities. Alternatively, biological technique could be considered as the best option due to low operational cost and flexibility in the application. Thus, this study is conducted to evaluate the feasibility of sulfide removal from synthetic wastewater by using an aerobic biological treatment in a sequencing batch reactor (SBR). The experiment was carried out by using 3.25L of SBR which was inoculated with inoculums originated from palm oil mill sludge. The synthetic wastewater was fed in the reactor and sodium sulfide was added as a source of sulfide with initial concentration between 150 and 300 mgL-1. After 50 days of operation, the present SBR simultaneously removed sulfide and COD with removal efficiencies of higher than 99 and 80%, respectively. The total suspended solid (TSS) and volatile suspended solid (VSS) in the effluent were kept stable at around 120 mgL-1 and 50 mgL-1, respectively. In conclusion, the aerobic activated sludge technology has the ability to remove simultaneously wastewater containing sulfide and COD with high removal efficiency. Thus, application of this technology to the real wastewater from petrochemical, tannery and photographic is highly recommended.